PENGARUH INTERNAL LOCUS OF CONTROL TERHADAP KEMATANGAN KARIR SISWA MADRASAH ALIYAH NEGERI 2 SAMARINDA - ., Eli Ariyani (MOTIVASI, 2014)
This study aims to determine whether there is a significant positif effect internal locus of control on the career maturity of students at Madrasah Aliyah Negeri 2 Samarinda. So that there are two relationships that will be investigated in this study, namely : 1) career maturity, 2) internal locus of control. The hypothesis that the proposed in this study is that there is a positive and significant effect internal locus of control on the career maturity of students. This study performed on all students class XII which consists of majors IPA I, IPA II, IPA III, IPS I, IPS II, AGAMA I, AGAMA II, BAHASA that amounts to 226 students. The results of this study effect internal locus of control on the career maturity of students shown from the analysis korelasi product moment, namely : 0,697 (p <0.05). Then the hypothesis this study be accepted. This study uses program SPSS 16.